The effect of teaching on the round table strategy on the achievement of fifth grade primary students in the reading subject - Salam Khaleel Al-Jubouri, Asma (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to identify (the effect of the round table strategy on the achievement of fifth-grade primary students in reading material, (by verifying the following zero hypothesis. There is a difference is statistically significant at the level of, (0.05 between the average degree of achievement students total of experimental studying reading material b strategy Aldrairh round and the average score achievement students Group b Ah control Alwata studied reading material in the usual way. Is determined by this research sample of students second grade average in school martyr Qasim Tarish in the district of the eastern province of Maysan Om and Doat book and reading texts to be taught to students of health in the second average in the course of Iraq for the second academic year 2018/2017.The current research is determined by a sample of fifth-grade primary students in the Pearl Primary School in Maysan Governorate and topics from the reading book scheduled by the Iraqi Ministry of Education to be taught to fifth-grade primary students. The researcher adopted the experimental approach with partial control of its relevance to the nature of the research .The current research sample consisted of (50 female students from the fifth elementary grade students and they were deliberately selected for the academic year 2018/2019 and this sample was randomly divided into two experimental groups the first group in which the students studied the reading subject according to the strategy of the circle of the circle and the second control group studied The female students were represented according to the usual method and Division A represented the experimental group and Division B represented the control group and all the researchers were statistically between the two research groups using the T-test for two independent samples .In the following variables (chronological age calculated months and Arabic language grades for the previous academic year 2017-2018 and by using the (Kay box in the academic achievement variable for parents .(After the researcher determined the topics of reading that will be studied during the duration of the experiment represented by the second course then the researcher formulated the behavioral goals for the specific topics of the reading subject prepared the teaching plans for them and presented them to a group of experts and specialists to judge their validity then the researcher made the necessary adjustments according to the observations of specialists. The researcher prepared an achievement test consisting of (20 twenty objective test items of the test type from multiple and the researcher confirmed the validity of the test the calculation of its reliability the discriminatory forces and the difficulty factor of the paragraphs. After the end of the experiment that started on Monday 25/2/2019 and the experiment ended on Tuesday 23/4/2019. the researcher applied the achievement test to the students of the experimental and control groups and after analyzing the results of the correct answers and statistically treating them using the T-test for two independent samples to know the significance of the difference at the level of 0.05 between the two research groups it was clear that the following. There is a difference with a statistically significant mechanism at the level of significance (0.05 between the average scores of fifth-grade primary students who studied the subjects of reading subject according to the round table strategy and the average scores of fifth-grade primary students who They studied according to the usual method of collection and in favor of the experimental group.